Beyond Global Food Supply Chains Crisis, Disruption, Regeneration - Stead, Victoria; Hinkson, Melinda (Springer Nature, 2022)
This open access book takes the upheaval of the global COVID-19 pandemic as a springboard from which to interrogate a larger set of structural, environmental and political fault lines running through the global food system. In a context in which disruptions to the production, distribution, and consumption of food are figured as exceptions to the smooth, just-in-time efficiencies of global supply chains, these essays reveal the global food system as one that is inherently disruptive of human lives and flourishing, and of relationships between people, places, and environments. The pandemic thus represents a particular, acute moment of disruption, offering a lens on a deeper, longer set of systemic processes, and shining new light on transformational possibilities.